A novel drop-based approach for fast thermal energy storage of phase change materials with a porous heater - Kiyak, Burak; Cosanay, Hakan; Biswas, Nirmalendu; Oztop, Hakan F.; Selimefendigil, Fatih (Elsevier, 2026)
The present work represents a comprehensive investigation of a drop-based melting dynamics of a phase change material (PCM) in a porous heating structure, exploring the combined influence of porous layer thickness, porosity, and heating temperature. Three distinct geometrical configurations pertaining to porous layer thicknesses (=5 mm, 10 mm, and 15 mm) are scrutinized systematically to assess the impact on the PCM melting dynamics. For each configurations, the impact of different porosity (e = 0.3, 0.6, and 0.9) of the porous layer on the melting process are analyzed. The porous region is maintained at constant temperatures (Th = 40 and 50 degrees C) to assess the impact of thermal conditions. The enthalpy-porosity approach is adapted to capture the phase transition behavior PCM; whereas the volume-of-fluid (VOF) technique is applied to solve the multiphase interactions, including the dripping phenomena of the melted PCM. The obtained results shown that a thinner porous layer (5 mm) and lower porosity (e = 0.3) provide a faster heat transfer and efficient phase change process, and thus superior thermal performance of the system. A quicker melting process is observed at elevated temperature (50 degrees C) due to higher thermal energy. For optimizing the fast melting and energy storage by the PCM, the thickness and porosity of the porous layer is pivotal. Higher thickness of the porous layer leads to a higher energy storage capacity during the initial stage, but it slower down the energy storage rate as the system stabilizes thermally. The major outcome from this investigation offers valuable insight into the coupled effects of thickness and porosity of the porous layer on enhanced melting process of PCM as well as heat energy storage in the systems.
Keywords: Energy Storage; Porous Heater; Volume-Of-Fluid; Heat Transfer; Phase Change Materials (Pcm)